Perilaku Membuang Makanan (Food Waste Behavior) Generasi Muda - Hadisza Anggreni; Maswadi Maswadi; Anita Suharyani (Universitas Galuh, 2026)
Food waste has become a major global issue due to its impacts on food security. Indonesia is among the countries generating high levels of food waste, making consumer behavior an important aspect to investigate, particularly among the younger generation. This study aimed to analyze food waste behavior among young people in Pontianak City using the Theory of Planned Behavior (TPB) framework. A quantitative descriptive approach was employed involving 60 senior high school students selected through probability sampling using a simple random sampling technique. Data were collected using structured questionnaires and analyzed descriptively through frequency distributions and percentages. The findings indicate that respondents generally exhibited a negative attitude toward food waste, considering food waste an undesirable behavior. Subjective norms also showed that family, peers, religious values, and cultural norms strongly encouraged respondents to avoid wasting food. Furthermore, perceived behavioral control revealed that most respondents believed they were capable of controlling their food consumption and preventing food waste. These findings suggest that although Pontianak contributes substantially to food waste generation in West Kalimantan, young people have demonstrated favorable awareness and self-control regarding food waste reduction. Therefore, efforts to reduce food waste should not only focus on increasing individual awareness but also strengthen household practices and social environments that support sustainable food consumption.